A coating method for rare earth hydrogen storage alloy powder for negative electrode of titanium dioxide coated nickel-metal hydride battery
By coating A2B7 rare earth hydrogen storage alloy powder with titanium dioxide, the problem of negative electrode capacity attenuation and poor circulation performance of hydrogen storage alloy is solved, and the high cycle life and rate performance of the battery is achieved, which is suitable for industrial applications.
Patent Information
- Application Number
- CN202211654318.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-22
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2042-12-22
AI Technical Summary
The A2B7 hydrogen storage alloy rapidly decays the capacity and poor circulation performance in the negative electrode of nickel-metal hydride battery, resulting in technical defects in battery application technology.
The coating method of A2B7 rare earth hydrogen storage alloy powder is used to coat the negative electrode of the nickel-metal hydride battery. By preparing titanium source solution, suspension, coating reaction and clean treatment, the titanium dioxide bag with enhanced conductivity is formed. Covering.
It significantly inhibits the capacity attenuation of A2B7 hydrogen storage alloy in strong alkali solution, improves the cycle life and rate performance of the battery, and has relatively simple process control and low equipment investment, which is suitable for large-scale production.
Smart Images

Figure CN116037918B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of nickel-metal hydride battery negative electrode materials, and specifically relates to a coating method of a titanium dioxide-coated rare earth hydrogen storage alloy powder for a nickel-metal hydride battery negative electrode, and in particular to a coating method of an A2B7 type rare earth hydrogen storage alloy powder for a titanium dioxide-coated nickel-metal hydride battery negative electrode. Background Art
[0002] Nickel-Metal Hydrogen Battery has been widely used in various electronic devices due to its advantages such as high volume energy density, excellent low temperature performance, strong overcharge resistance or no memory effect. However, the addition of Co element in the commercial AB5 type alloy reduces the market competitiveness. Compared with the AB5 type, the A2B7 type hydrogen storage alloy, especially the Ln-Mg-Ni system (Ln refers to mixed rare earth elements) hydrogen storage alloy, has a catalyst-like effect on the hydrogen absorption ability of magnesium, which makes the alloy of this system have a higher gaseous hydrogen storage capacity (1.8wt.%), as well as good activation performance and high rate discharge performance. Therefore, both from the perspective of performance and market competitiveness, it is a candidate negative electrode material for nickel-metal hydride batteries.
[0003] Although A2B7 type hydrogen storage alloy has entered the practical stage, it is easy to oxidize and corrode in strong alkaline solution, resulting in alloy pulverization, accelerating the corrosion of the alloy negative electrode and the loss of active substances, and ultimately leading to rapid capacity decay of the alloy negative electrode and poor cycle performance. Therefore, the preparation means and modification methods of this type of alloy still need to be further improved, which is of great significance to improving the production technology level and comprehensive performance of this type of alloy.
[0004] In recent years, researchers have adopted a variety of new technologies and methods to improve the comprehensive performance of this type of hydrogen storage alloy. Common methods for optimizing alloy systems include element substitution in alloys, preparation of composite alloys, regulation of heat treatment regimes to control alloy composition, improvement of material performance, and use of common ion effects to improve the distribution of key ions in the double layer in the anode region. In addition, surface treatment of alloys is also an effective strategy. This method is simple and easy to operate, has low manufacturing costs, and is beneficial to improving the corrosion resistance and cycle stability of alloys in strong alkaline electrolytes. Titanium dioxide (TiO2) has the characteristics of low expansion rate, high mechanical stability, and acid and alkali resistance, which makes it show great potential as a good composite coating component. If the TiO2 phase can be coated on the surface of the hydrogen storage alloy to protect the negative electrode from electrolyte invasion and inhibit side reactions, it may be possible to obtain better negative electrode active material materials with far more advantages than disadvantages in the performance balance optimization process.
[0005] However, it is not easy to coat TiO2 on the surface of hydrogen storage alloy for use as the negative electrode active material of the battery; colleagues in the industry often say: "Electricity comes first" in batteries, or in addition to the two materials of the diaphragm and the shell, other materials in the battery must have good conductivity, so that the battery can have low internal resistance, high discharge power and released electrical energy, low charging energy barrier, energy saving and long service life. Common stoichiometric titanium dioxide is well-known as "titanium dioxide", which is widely used in white pigments. It has very weak conductivity or "non-conductive". Obviously, it is against the common sense of battery design to coat this titanium dioxide with its own conductive hydrogen storage alloy powder. The titanium dioxide used in the battery plate must be conductive titanium dioxide or conductively treated titanium dioxide. The earliest inventor of increasing the conductivity of titanium dioxide was Harold R. of the United States. This was disclosed in the US Patent No. 2,940,941 (application number) published by the United States Patent and Trademark Office on June 14, 1960. The title of the patent is "Modified Titanium Dioxide and Preparation Method". The core invention of the invention is: the discovery of obtaining rutile structure titanium dioxide by burning titanium dioxide at a high temperature of 1000°C to 1400°C to improve its conductivity was improved to a burning temperature of 600°C to 900°C. Since then, new methods for increasing the conductivity of titanium dioxide or obtaining conductive titanium dioxide have increased day by day. Effective methods include depleting the "oxygen" in the stoichiometric ratio of titanium dioxide, such as adjusting the stoichiometric ratio to TiO2 in the process of manufacturing TiO2. 1.98 , the "oxygen" in this titanium dioxide is slightly depleted, and its conductivity increases sharply; there are some other effective methods, such as: US 9,493,883B2 disclosed by the United States Patent and Trademark Office; US 8,827,083B2; US10,205,194B2; US7,514,124B2; US7,514,124B2; The application numbers published by the State Intellectual Property Office are 201410040976.1, 201510666889.1, 201510081677.7, 201711136999.2, etc. These representative inventions all disclose effective methods for improving the conductivity of titanium dioxide.
[0006] However, the application of titanium dioxide in nickel-metal hydride batteries is mainly used as a positive electrode material additive to improve the high temperature performance and cycle stability of nickel-metal hydride batteries. On May 6, 2015, the State Intellectual Property Office published an invention patent entitled "High-power wide-temperature power nickel-metal hydride battery" with publication number CN104600375A, which improves the charge and discharge performance of nickel-metal hydride batteries under high temperature conditions. Another patent published by the Japan Patent Office on March 19, 2020, "Positive electrode of alkaline secondary battery and alkaline secondary battery including the positive electrode" (publication number: JP2020043010A), proposes that the use of positive electrode additives (titanium dioxide, etc.) containing a conductive network can suppress the rapid decline in discharge characteristics. However, neither of them involves the effect of titanium dioxide on the negative electrode hydrogen storage alloy during the electrochemical reaction process. At present, there is no related work reporting the application of titanium dioxide in negative electrode materials.
[0007] In summary, for the application of A2B7 hydrogen storage alloys in nickel-metal hydride battery negative electrodes, the main technical barriers currently encountered in the balanced optimization of battery negative electrode materials are the rapid capacity decay of the alloy negative electrode and poor cycle performance. This technical barrier has not been overcome more fundamentally, which constitutes a technical defect in battery application technology. We need to find a coating agent that can be used in a strong alkaline battery environment, and the coating agent has the "performance bonus" of full decomposition, rapid capacity decay, and poor cycle performance. The weight gain of the coating agent has the disadvantages of negative effects such as reduced weight-to-capacity ratio of the negative electrode active material and weakened conductivity. In the process of weighing the pros and cons, finding a new coating agent and coating method with far more advantages than disadvantages is very attractive to battery companies and hydrogen storage alloy powder manufacturers using A2B7 hydrogen storage alloys. Summary of the invention
[0008] Regarding the application of A2B7 hydrogen storage alloy in the negative electrode of nickel-metal hydride batteries, in the process of balancing and optimizing the battery negative electrode materials, the technical defects of the alloy negative electrode such as fast capacity decay and poor cycle performance, and the lack of "bonus" after overcoming this technical defect far outweigh the existing industry difficulties of new coating agents and corresponding coating methods, which have the disadvantages of reduced weight specific capacity of negative electrode active materials and weakened conductivity due to the increase in weight of the coating agent.
[0009] The purpose of the present invention is to provide a method for coating a titanium dioxide-coated rare earth hydrogen storage alloy powder for a negative electrode of a nickel-metal hydride battery; in particular, to provide a surface coating method for an A2B7 type hydrogen storage alloy negative electrode material for a nickel-metal hydride battery that can be widely accepted by the battery industry and improves the cycle life and rate performance of the A2B7 type hydrogen storage alloy without negatively affecting the battery industry.
[0010] The technical solution for achieving the purpose of the present invention, or the technical solution for a method for coating a rare earth hydrogen storage alloy powder for a negative electrode of a nickel-metal hydride battery with titanium dioxide, mainly comprises the following four steps:
[0011] Step 1: Prepare titanium source solution: select deionized water as solvent and chemically pure ammonium fluorotitanate as solute, prepare at room temperature, and the solution ratio is: solvent weight: solute weight = 1: 0.01483.
[0012] Step 2: Prepare the suspension: The liquid part of the suspension is the titanium source solution, and the solid powder part is the A2B7 rare earth hydrogen storage alloy powder. Prepare at room temperature. The ratio of the suspension is: the weight of the titanium source solvent: the weight of the solid powder = 1: x. Control the stirring time of the motor propeller stirrer to be t1.
[0013] The range of x value in this step is: x=0.0167±0.0033; the reason why the x value is controlled within this range is that after a certain amount of titanium source, the value of x is too large, or the amount of A2B7 type rare earth hydrogen storage alloy powder is too much, and the titanium in the coating agent is relatively scarce, and it is impossible to coat all the particles of the hydrogen storage alloy powder, so it is easy for a part of the hydrogen storage alloy powder to not be coated, and vice versa. The negative effect is that the coating layer coating the hydrogen storage alloy powder is too thick, which not only causes a waste of titanium source and increases the cost of manufacturing raw materials, but also reduces the weight specific capacity of the negative electrode active material too much during the battery manufacturing process, thereby resulting in a significant decrease in the weight specific energy and volume specific energy of the battery.
[0014] The range of t1 in this step is: t1 = 5 minutes ± 2 minutes; the reason why the t1 value is controlled in this range is that the fundamental purpose of the stirring is to make the A2B7 type rare earth hydrogen storage alloy powder and the ammonium fluorotitanate in the solution fully wetted or in contact, and the two form a suspension for the subsequent construction of an ideal sol-gel reaction environment; if the t1 value is too large, or the stirring time is too long, not only the processing time cost and the motor power consumption cost will be increased, but also the A2B7 type rare earth hydrogen storage alloy powder will be corroded too deeply by the ammonium fluorotitanate, the rare earth hydrogen storage alloy powder will be seriously wasted, and the dissolved side reaction products will also have a negative impact on the subsequent sol-gel reaction; on the contrary, if the t1 value is too small, or the stirring time is too short, the ammonium fluorotitanate in the solution and the surface of the rare earth hydrogen storage alloy powder are not fully wetted, the constructed suspension has poor stability, the subsequent sol-gel reaction environment is poor, and the reaction quality is poor.
[0015] In this step, the chemical expression of the A2B7 type rare earth hydrogen storage alloy powder material in the "solid powder part selects A2B7 type rare earth hydrogen storage alloy powder" is Ln 0.8 Mg 0.2 Ni 3.5 Al 0.3 Zr 0.05; The Taylor standard sieve screening system for powder particle size is 200 mesh ± 50 mesh or 300 mesh ± 50 mesh.
[0016] The so-called "Tyler standard sieve screening system for powder particle size is 200 mesh ± 50 mesh or 300 mesh ± 50 mesh" can also be: if you want to obtain A2B7 rare earth hydrogen storage alloy powder with 200 mesh ± 50 mesh, select one 150 mesh standard sieve and one 250 mesh standard sieve, place the former on top of the latter, pour the rare earth hydrogen storage alloy powder from the top of the sieve for sieving, take the powder in the middle of the two sieves, or the powder in the lower sieve of 250 mesh and use it. Similarly: to obtain A2B7 rare earth hydrogen storage alloy powder with 300 mesh ± 50 mesh, select one 250 mesh standard sieve and one 350 mesh standard sieve, and the subsequent screening operations are no longer redundant.
[0017] Step 3: Coating reaction: The promoter of the coating reaction is chemically pure boric acid solid powder, the reaction stock solution is the suspension containing A2B7 rare earth hydrogen storage alloy powder in the second part, the reaction temperature is room temperature, the ratio of promoter to solvent in the suspension is: the weight of solvent in the suspension: the weight of promoter = 1:y, the stirring time of the motor propeller stirrer is controlled to be t2, and the time interval of stopping stirring and standing until all the precipitates in the coating reaction system are precipitated to the bottom of the reactor is t3.
[0018] The range of the y value in this step is: y=0.0123±0.0003. The reason for controlling the y value in this range is that after a certain amount of titanium source, if the y value is too large, or the amount of the promoter boric acid is too much, not only will the reaction speed be too fast, resulting in poor quality of the coating layer, but also the undesirable side reactions will increase sharply or cause the coating reaction to fail. The "poor quality of the coating layer" here is obviously the same as the principle of electroplating. In order to obtain a good coating by electroplating, the cathode current density is too large, the target atoms of the coating are quickly accumulated, and the kinetic atomic arrangement time is lacking. The coating cannot be bright and firm. Similarly, the promoter boric acid promotes the chain reaction of ammonium fluorotitanate so that the dissociated titanium ions or titanium atoms therein are accumulated too quickly on the surface of the A2B7 type rare earth hydrogen storage alloy powder particles. The coating obtained on the surface of the A2B7 type rare earth hydrogen storage alloy powder particles cannot be firm and smooth, and a firm, smooth and uniform coating is the main component of the coating quality.
[0019] On the contrary, if the value of y is too small, or the amount of the promoter boric acid is too small, the thermodynamic free energy of the reaction step of dissociation of ammonium fluorotitanate into titanium ions or titanium atoms will be low. In the extreme case, the thermodynamic reaction cannot occur, resulting in the failure of the reaction at the beginning of the series of reactions. At the same time, the small entropy value in kinetics also causes the negative effect of "wind driving the fire and fire helping the wind" at the level of difficulty in reaction.
[0020] In short, the y value in this step cleverly corresponds to the amount of ammonium fluorotitanate, a salt that provides the source of titanium. It is not difficult for colleagues in the synthetic chemistry industry to guess that controlling this y value is one of the key technologies and the main "hiding place" of the "technology know how".
[0021] The range of t2 in this step is: t2 = 9 hours ± 3 hours. Obviously, colleagues in the synthetic chemistry industry, based on the electroplating coating quality control principles listed above, the t2 value here, like the electroplating time control, is an important kinetic factor in the quality control of the coating layer. The coating layer and the electroplating layer are controlled according to the similar principle of kinetic control of "the two lines are like mountains apart, but the principles are the same". The details of whether the method of the present invention is successful or the quality control will be omitted here if the t2 value is too large or too small.
[0022] The range of t3 in this step is: t3 = 6 hours ± 2 hours. The reason for taking this t3 value and range is not difficult for synthetic chemists to understand. The reaction system here is a sol-gel system. If the t3 value is too large or too small, the precipitation of alloy powder-coated particles relying on the low-cost vertical gravity of the earth and the static sedimentation relying on the static time will affect the product yield and the subsequent cleaning difficulty. It will not be repeated here.
[0023] Step 4: Cleaning treatment of the coating: The three consecutive steps of the cleaning treatment are: Ⅰ, centrifugal dehydration of the precipitate, or drying the precipitate obtained by the third step of the coating reaction with a centrifuge, Ⅱ, precipitate washing, or rinsing the precipitate dried by the centrifuge with deionized water three times, Ⅲ, vacuum drying, or placing the precipitate rinsed with deionized water into a vacuum drying oven, starting a mechanical pump to evacuate and setting the drying temperature to T1, and setting the drying time to t4; after the oven is cooled to room temperature, argon is filled in, and the door of the oven is opened to take out the dried product to obtain the target product, which is titanium dioxide coated A2B7 type rare earth hydrogen storage alloy powder for the negative electrode of nickel-metal hydride battery.
[0024] The range of T1 in this step: T1 = 50°C ± 10°C; the range of t4 in this step: t4 = 12 hours ± 4 hours.
[0025] In view of the fact that drying temperature and drying time are common means of product processing in the field of chemical synthesis, the principle is nothing more than to preferably select an efficient and high-capacity drying system with short time consumption, low energy efficiency and high product quality according to the physicochemical properties of the dried product and the product quality requirements; the influence of too large or too small T1 and t4 values of this step on the quality of the final product of the present invention is not repeated here.
[0026] Obviously, whether the titanium dioxide-coated A2B7 rare earth hydrogen storage alloy powder coating for the negative electrode of nickel-metal hydride battery obtained through the above four steps meets the expectations of the invention still requires professional and necessary characterization; the next step, or it can be called the fifth step - relevant characterization.
[0027] Step 5: Related characterization: The characterization closely related to the practicality of the target product, or the coating of the rare earth hydrogen storage alloy powder for the negative electrode of the nickel-metal hydride battery coated with titanium dioxide, in the nickel-metal hydride battery is the electrochemical characterization, specifically, the comprehensive electrochemical performance of the coating of the A2B7 type rare earth hydrogen storage alloy powder for the negative electrode active material of the nickel-metal hydride battery, using the simulated battery characterization commonly used in the battery industry to characterize the active material for the battery plate or the positive and negative active materials of the electrode, using a strict control test method, or using the original powder of the uncoated A2B7 type rare earth hydrogen storage alloy as a blank or standard, under the same external environment, the coating of the present invention is subjected to a convincing electrochemical characterization of "comparing goods with goods".
[0028] Another relevant characterization is to use advanced modern instruments to characterize the microstructure of the target coating. Similarly, the comparative characterization is more credible. Specific relevant characterizations are disclosed in the detailed embodiments of the present invention, the drawings and the description of the drawings, and are not redundant here.
[0029] The beneficial effects of the present invention are as follows:
[0030] First, the coating process is relatively short and belongs to the "short process" technology. At the same time, the three stages of the main coating process (the first three steps of the present invention) are easy to design to be carried out in the same reactor, with less equipment investment. This technology with short process and low investment is conducive to the production and use of hydrogen storage alloy production plants and is also suitable for use by A2B7 type hydrogen storage alloy battery production plants.
[0031] Second, the effect of inhibiting the capacity decay of the A2B7 type hydrogen storage alloy in the nickel-metal hydride battery in the strong alkaline solution is relatively desirable, as shown in the attached Figure 2 The comparison effect revealed in the figure shows that with a suitable coating process, as long as the simulated battery cycle is less than 20 cycles, its weight specific capacity is higher than the uncoated blank (curve 1), and it is still higher than the blank until the cycle is 400 cycles. Even with a relatively poor coating process, it can be higher than the blank at 280 cycles and its single gram weight specific capacity is still 22 mAh / g higher than the blank at 400 cycles; the invention purpose of the present invention to inhibit the capacity decay of A2B7 is achieved.
[0032] Thirdly, the process control is not difficult, and the raw materials are easily available, which is conducive to the stable and large-scale production of the production plant. In addition, the coated product of the present invention has little negative impact on the rate performance, and under appropriate coating process conditions, the negative impact can even be ignored, which ensures the number of selected products for power battery production plants using A2B7 type hydrogen storage alloys. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 It is a process flow chart of the present invention "a method for coating A2B7 type rare earth hydrogen storage alloy powder for anode of a nickel-metal hydride battery coated with titanium dioxide".
[0034] Figure 2 This is a comparative test result of the cycle performance of the nickel-metal hydride battery negative electrode material obtained by the present invention at 375 mA / g.
[0035] Curve (1) in this figure is the "blank" required for the control experiment, which is the cycle performance curve of the A2B7 hydrogen storage alloy powder without coating; Curve (2) is the cycle performance curve of the A2B7 hydrogen storage alloy powder coated with titanium dioxide under the process conditions of "Example 1" of the present invention; Curve (3) is the cycle performance curve of the A2B7 hydrogen storage alloy powder coated with titanium dioxide under the process conditions of "Example 2" of the present invention.
[0036] Depend on Figure 2 Comparison of the three curves shows that the new process of titanium dioxide coating A2B7 hydrogen storage alloy powder of the present invention is effective in inhibiting the rapid capacity decay of A2B7 hydrogen storage alloy powder in nickel-metal hydride batteries. The appropriate coating process similar to curve (2) has a higher weight capacity than the uncoated blank (curve 1) in less than 20 cycles, and remains higher than the blank until 400 cycles. Although the coated curve 3 is higher than the blank only after 280 cycles, its single gram weight capacity is 22mAh / g higher than the blank after 400 cycles. It can also be seen that the coating layer of curve (3) is too thick, and the capacity is lower than the blank before 280 cycles. This suggests that the coating process should pay attention to avoid too thick a coating layer.
[0037] Figure 3 It is a representative XRD diagram of the present invention "a method for coating A2B7 type rare earth hydrogen storage alloy powder for a negative electrode of a nickel-metal hydride battery coated with titanium dioxide" under different process systems.
[0038] Curve (3) in this figure is the "blank" required for the control experiment, which is the XRD curve of the A2B7 hydrogen storage alloy powder without coating; Curve (2) is the XRD curve of the A2B7 hydrogen storage alloy powder coated with titanium dioxide under the process conditions of "Example 2" of the present invention; Curve (1) is the XRD curve of the A2B7 hydrogen storage alloy powder coated with titanium dioxide under the process conditions of "Example 1" of the present invention.
[0039] From the comparison of the three curves, it can be seen that the coating process of the A2B7 type rare earth hydrogen storage alloy powder for the negative electrode of the nickel-metal hydride battery does not change the crystal phase structure of the rare earth hydrogen storage material. It is well known in the industry that for Ln 0.8 Mg 0.2 Ni 3.5 Al 0.3 Zr 0.05 The main phase of this A2B7 rare earth hydrogen storage alloy is composed of LaNi5 phase and La2Ni7 phase. The crystal phase structure of the main phase does not change before and after coating, and even the weak drift of the "three strong peaks" relative to the blank does not exist. This shows that the coating process of the present invention does not have the worry or defect of changing the crystal structure of the main alloy due to the coating process.
[0040] Figure 4 are selected representative scanning electron microscope (SEM) images of the present invention.
[0041] The morphology image (3) in this figure is the morphology image of the "blank" required for the control experiment, which is also the morphology image of the particle surface of the A2B7 hydrogen storage alloy powder without coating under the scanning electron microscope. The morphology image (2) is the morphology image of the particle surface of the A2B7 hydrogen storage alloy powder coated with titanium dioxide under the process conditions of "Example 2" of the present invention; the morphology image (1) is the morphology image of the particle surface of the A2B7 hydrogen storage alloy powder coated with titanium dioxide under the process conditions of "Example 1" of the present invention.
[0042] By comparing the three morphological images, it can be seen that: compared with Figure (3), the surface of the hydrogen storage alloy in Figures (1) and (2) changes from smooth to rough, and there is an obvious coating layer. The coating of the spherical particles is particularly "conspicuous". The thicker the coating layer, the more coatings there are on the spherical particles. For example, in Figure (2), the spherical particles have more coatings than those in Figure (1). However, it is worth noting that: if the coating layer is too thick, cracked alloy powder particles can be found in the sampling area under a scanning electron microscope. The mechanism of its occurrence and its positive or negative effects are still worthy of further study.
[0043] Figure 5 It is a representative X-ray photoelectron diffraction (XPS) pattern of the present invention.
[0044] Curve (3) in this figure is the "blank" required for the control experiment, which is the XPS curve of the A2B7 hydrogen storage alloy powder without coating; Curve (1) is the XPS curve of the A2B7 hydrogen storage alloy powder coated with titanium dioxide under the process conditions of "Example 1" of the present invention; and Curve (2) is an enlarged curve of a small section of the curve intercepted by curve (1), specifically: Curve (2) is an enlarged curve of a small section of the curve at 454 to 470 electron volts under the energy bombardment of 200 to 600 electron volts of curve (1).
[0045] By comparing curve (3) with curve (1), it can be seen that the coated A2B7 rare earth hydrogen storage alloy powder for the negative electrode of the nickel-metal hydride battery curve (1) has an increased Ti content compared to the XPS curve (3) of the corresponding uncoated powder particles. 4+ The characteristic peak of Ti 2p is shown in Figure 2. In order to make the peak more intuitive, curve (2) is enlarged to reveal the Ti element as Ti 4+ The existence of the alloy surface is more certain, and combined with small-angle X-ray diffraction and other instrument characterization, the combined results preliminarily reveal that the alloy surface Ti 4+ It mainly combines with the O element and is coated on the surface of the hydrogen storage alloy material in the form of TiO2. DETAILED DESCRIPTION
[0046] The following examples are provided to further illustrate the present invention, rather than to limit the present invention.
[0047] Example 1
[0048] Step 1: Prepare titanium source solution: select deionized water as solvent and chemically pure ammonium fluorotitanate as solute, prepare at room temperature, and the solution ratio is: solvent weight: solute weight = 1: 0.01483.
[0049] Step 2: Prepare the suspension: The liquid part of the suspension is the titanium source solution, and the solid powder part is the A2B7 rare earth hydrogen storage alloy powder. Prepare at room temperature. The ratio of the suspension is: the weight of the titanium source solvent: the weight of the solid powder = 1: x. Control the stirring time of the motor propeller stirrer to be t1.
[0050] The preparation parameters selected in this step are: x=0.0167, t1=5 minutes.
[0051] The material and particle size of the solid powder in this step are as follows: The chemical expression of the A2B7 rare earth hydrogen storage alloy powder is Ln 0.8 Mg 0.2 Ni 3.5 Al 0.3 Zr 0.05 ; Powder particle size is 200 mesh ± 50 mesh.
[0052] The specific operation to obtain the A2B7 rare earth hydrogen storage alloy powder with a particle size range of 200 mesh ± 50 mesh is as follows: select one 150 mesh Taylor standard sieve and one 250 mesh Taylor standard sieve, place the 150 mesh standard sieve on top of the 50 mesh standard sieve, pour the rare earth hydrogen storage alloy powder from the top of the sieve for sieving, and use the powder between the two sieves, or the powder in the lower sieve of 250 mesh.
[0053] Step 3: Coating reaction: The promoter of the coating reaction is chemically pure boric acid solid powder, the reaction stock solution is the suspension containing A2B7 rare earth hydrogen storage alloy powder in the second part, the reaction temperature is room temperature, the ratio of promoter to solvent in the suspension is: the weight of solvent in the suspension: the weight of promoter = 1:y, the stirring time of the motor propeller stirrer is controlled to be t2, and the time interval of stopping stirring and standing until all the precipitates in the coating reaction system are precipitated to the bottom of the reactor is t3.
[0054] The synthetic reaction conditions adopted in this step are: y=0.0123, t2=9 hours, t3=6 hours.
[0055] Step 4: Cleaning treatment of the coating: The three consecutive steps of the cleaning treatment are: Ⅰ, centrifugal dehydration of the precipitate, or drying the precipitate obtained by the third step of the coating reaction with a centrifuge, Ⅱ, precipitate washing, or rinsing the precipitate dried by the centrifuge with deionized water three times, Ⅲ, vacuum drying, or placing the precipitate rinsed with deionized water into a vacuum drying oven, starting a mechanical pump to evacuate and setting the drying temperature to T1, and setting the drying time to t4; after the oven is cooled to room temperature, argon is filled in, and the door of the oven is opened to take out the dried product to obtain the target product, which is titanium dioxide coated A2B7 type rare earth hydrogen storage alloy powder for the negative electrode of nickel-metal hydride battery.
[0056] In this step, the two parameters of drying temperature and drying time are specifically selected as: T1 = 50°C, t4 = 12 hours.
[0057] Step 5: Relevant Representation
[0058] First, the titanium dioxide-coated A2B7 rare earth hydrogen storage alloy powder for the negative electrode of the nickel-metal hydride battery was taken out from the oven, and the comparative test method and the method commonly used in the battery industry to characterize the comprehensive electrochemical performance of the active material for the battery plate in the simulated battery were used to characterize it. The specific characterization operation, i.e., the steps are as follows:
[0059] Ⅰ. Blank selection: original powder of A2B7 type rare earth hydrogen storage alloy without coating.
[0060] Ⅱ. Material selection, design and molding of main components of simulated batteries:
[0061] ⅰ. Material selection, design and molding of the positive electrode of the simulated battery: The positive electrode of the simulated battery is a commercially available sintered nickel anode, which is cut into plates according to the size of the plate that can be loaded into the battery shell. Then, according to the unit area capacity parameters given in the instructions of the manufacturer selling the sintered nickel anode, the number of the cut plates is selected according to the specification that the positive electrode capacity of the simulated battery to be assembled is greater than 6 times the negative electrode capacity. The obtained several sintered nickel anodes are welded together with a pulse electric welder, and the cut nickel sheets are used as anode lead wires, which are welded to the anode with a pulse electric welder.
[0062] ⅱ. Material selection, design and molding of simulated battery negative electrode:
[0063] Selection of negative electrode battery active materials First, the titanium dioxide-coated A2B7 rare earth hydrogen storage alloy powder for nickel-metal hydride battery negative electrode obtained under different preparation conditions is selected, and then the corresponding uncoated A2B7 rare earth hydrogen storage alloy powder is selected, which is used for the blank of comparison characterization.
[0064] Commercially available carbonyl nickel powder with the brand T255 was selected as the negative electrode forming agent and also as a conductive agent. The carbonyl nickel powder was weighed 6 times the weight of the negative electrode battery active material, and the two powders were evenly mixed in a mortar and placed in the mold of a tablet press. Then, the negative electrode disc was formed by cold pressing. The cut nickel sheets were also used as electrode lead wires, and were welded to the disc with a pulse electric welder to obtain a simulated battery negative electrode.
[0065] ⅲ. Material selection, design and preparation of simulated battery electrolyte: Select commercially available analytically pure potassium hydroxide and lithium hydroxide reagents, and prepare them in a ratio of 6 moles of potassium hydroxide to 1 mole of lithium hydroxide in 1 liter of electrolyte. The obtained electrolyte is sealed and ready for use.
[0066] ⅳ. Material selection, design and processing of the diaphragm in the simulated battery: The diaphragm is a commercially available polypropylene sulfonated grafted membrane, which is cut and used in accordance with the principle that the size is not smaller than the sintered nickel anode block.
[0067] III. Assembly of simulated battery: construct the positive electrode sheet, negative electrode sheet and separator into a "sandwich" type battery cell, or place the negative electrode sheet in the middle of the "sandwich" type battery cell, sandwich the negative electrode between two positive electrodes, and separate the positive and negative electrodes with a separator. The "sandwich" type battery cell is clamped with a clamp and placed in the battery shell, and the electrolyte is injected. The upper cover of the shell is sealed, and the battery electrode lead wires outside the shell are cleaned. The lead wires are connected to the positive and negative electrode wires of the battery comprehensive tester, and the simulated battery assembly is completed.
[0068] IV. Charge and discharge system: Select the "voltage limit" control among the "three limits" control of the battery comprehensive tester, and set the upper limit of charge to 1.6V; the lower limit of discharge, or the discharge cut-off voltage, is set to 0.8V; set the charge and discharge current according to different current density targets; set the automatic charge and discharge conversion time interval to 1 minute. Before the first charge and discharge, the simulated battery needs to stand for 24 hours so that the positive and negative electrodes and the diaphragm in the battery cell are fully wetted by the electrolyte; measure the weight specific capacity of the active material at different current densities.
[0069] Ⅴ. Characterization of capacity decay of negative electrode active material: On the comprehensive battery tester, the programming used is: the charge and discharge current density is set to 375mA / g, the charge and discharge voltage of the "voltage limit" control program is 1.6V and 0.8V respectively, or the upper limit of charge is set to 1.6V; the lower limit of discharge (discharge cut-off voltage) is set to 0.8V, and the battery life is measured by cyclic charge and discharge.
[0070] VI. Comparative test results:
[0071] ⅰ. Comparative measurement results of capacity decay of negative electrode active material:
[0072] At a charge and discharge current density of 375 mA / g, the charge and discharge voltage limit of 1.6 V to 0.8 V was selected to perform charge and discharge cycles. The weight specific capacity data of the negative electrode active material after 400 cycles was selected, and the results were as follows:
[0073] The weight specific capacity of the titanium dioxide coated A2B7 rare earth hydrogen storage alloy powder of the present invention is 218.2 mAh / g. The specific cycle curve shows that the Figure 2 The curve (2) shows that the original powder of A2B7 rare earth hydrogen storage alloy without coating, or "blank", has a weight specific capacity of 190.2 mAh / g. The specific cycle curve reveals that Figure 3 Curve (1); it can be seen that the purpose of the invention is achieved.
[0074] ii. The results of comparative determination of the weight specific capacity of the active material at different current densities are listed in the second column (blank) and the third column (this embodiment) of Table 1, respectively.
[0075] Second, microstructure characterization
[0076] Take out the coating of A2B7 type rare earth hydrogen storage alloy powder for the negative electrode of nickel-metal hydride battery coated with titanium dioxide from the oven, and use the control test method to characterize the microstructure. The sampling of the microstructure characterization is to randomly select the coated sample and the corresponding blank. However, not every batch of samples are selected. Only representative samples are selected from the samples obtained by changing the process conditions for microstructure characterization. Similarly, the characterization means also select closely related representative means for characterization. The representative means selected by the present invention are XRD (X-ray powder diffraction), SEM (scanning electron microscope) and XPS (X-ray photoelectron diffraction). The specific characterization results are as follows:
[0077] VII. XRD characterization results: revealing Figure 3 , the attached Figure 3 Curve 1 in the figure is the XRD curve of the A2B7 type rare earth hydrogen storage alloy powder coated with titanium dioxide according to the present invention, while the XRD curve of the original A2B7 type rare earth hydrogen storage alloy powder without coating, or the "blank" XRD curve, is the XRD curve of the titanium dioxide coated A2B7 type rare earth hydrogen storage alloy powder. Figure 3 Curve 3 in FIG. 1 shows that the coating process did not damage the main phase structure of the A2B7 rare earth hydrogen storage alloy.
[0078] Ⅷ. SEM characterization results: revealing Figure 4 The morphology image (3) in this figure is the "blank" morphology image required for the control experiment, or the morphology image of the particle surface of the A2B7 hydrogen storage alloy powder without coating under the scanning electron microscope. The morphology image (1) is the morphology image of the particle surface of the A2B7 hydrogen storage alloy powder coated with titanium dioxide under the process conditions of this embodiment; from the comparison of the two morphology images, it can be seen that: compared with Figure (3), the surface of the hydrogen storage alloy in Figure (1) changes from smooth to rough, with a clear coating layer, and the coating of the coating layer close to the spherical particles is particularly "conspicuous".
[0079] IX. XPS characterization results: It reveals that Figure 5 Curve (3) in this figure is the "blank" required for the control experiment, which is the XPS curve of the A2B7 hydrogen storage alloy powder without coating; Curve (1) is the XPS curve of the A2B7 hydrogen storage alloy powder coated with titanium dioxide under the process conditions of this embodiment; and Curve (2) is an enlarged curve of a small section of the curve intercepted by curve (1), specifically: Curve (2) is an enlarged curve of a small section of the curve intercepted at 454 to 470 electron volts under the energy bombardment of 200 to 600 electron volts of curve (1).
[0080] By comparing curve (3) with curve (1), it can be seen that the coated A2B7 rare earth hydrogen storage alloy powder for the negative electrode of the nickel-metal hydride battery curve (1) has an increased Ti content compared to the XPS curve (3) of the corresponding uncoated powder particles.4+ The characteristic peak of Ti 2p is shown in Figure 2. In order to make the peak more intuitive, curve (2) is enlarged to reveal the Ti element as Ti 4+ The existence of the form is more certain.
[0081] Example 2
[0082] The difference from Example 1 is:
[0083] Ⅰ. Preparation conditions The conditions different from those in Example 1 include:
[0084] i. Preparation parameters in the second step of preparing the suspension: x = 0.0134, t1 = 7 minutes
[0085] ii. The synthetic reaction condition parameters in the third step of coating reaction are selected as follows: y = 0.0126, t2 = 12 hours, t3 = 8 hours
[0086] ⅲ. The preparation parameters in the fourth step of the coating cleaning process are selected as follows: T1 = 40°C, t4 = 8 hours.
[0087] II. The coating object is different from Example 1 in that the particle size of the solid powder in the suspension prepared in the second step is selected to be 300 mesh ± 50 mesh.
[0088] III. The electrochemical performance results obtained are different from those of Example 1 in that:
[0089] ⅰ. The comparative measurement results of the capacity decay of the negative electrode active material reveal that Figure 2 Curve (3) of curve 3 is higher than the blank at 280 cycles, but at 400 cycles, its single gram weight capacity is 22 mAh / g higher than the blank. It can also be seen that the coating layer of curve (3) is too thick. Before 280 cycles, the capacity is lower than the blank. This suggests that the coating process should pay attention to avoid too thick coating layer
[0090] ii. Comparative determination of the weight specific capacity of the active material at different current densities: This example is listed in the fourth column of Table 1.
[0091] IV. The obtained microstructure characterization results are different from those of Example 1 in that:
[0092] ⅰ, XRD characterization results: revealing Figure 3 Curve 2.
[0093] ii. SEM characterization results: revealing Figure 4 Figure 2.
[0094] iii. XPS characterization results: In this example, no sample was selected for XPS control characterization.
[0095] The rest is the same as in Example 1.
[0096] Example 3
[0097] The difference from Example 1 is:
[0098] Ⅰ. Preparation conditions The conditions different from those in Example 1 include:
[0099] i. Preparation parameters in the second step of preparing the suspension: x = 0.02, t1 = 3 minutes
[0100] ii. The synthetic reaction condition parameters in the third step of coating reaction are selected as follows: y = 0.0120, t2 = 6 hours, t3 = 4 hours
[0101] ⅲ. The preparation parameters in the fourth step of the coating cleaning process are selected as follows: T1 = 60°C, t4 = 16 hours.
[0102] II. The coating object is different from Example 1 in that the particle size of the solid powder in the suspension prepared in the second step is selected to be 300 mesh ± 50 mesh.
[0103] III. The electrochemical performance results obtained are different from those of Example 1 in that:
[0104] i. Results of comparative determination of the weight specific capacity of active materials at different current densities: This example is listed in the fifth column of Table 1.
[0105] ii. This example does not perform other electrochemical performance characterizations as in Example 1.
[0106] IV. The obtained microstructure characterization results are different from those of Example 1 in that:
[0107] This embodiment does not perform sample characterization of the microstructure as in Embodiment 1.
[0108] The rest is the same as in Example 1.
[0109] Table 1. Gravimetric specific capacity of blank and Examples 1, 2, and 3 at different current densities
[0110]
[0111]
Claims
1. A method for coating a titanium dioxide-coated rare earth hydrogen storage alloy powder for a negative electrode of a nickel-metal hydride battery, characterized in that: It includes the following four steps: Step 1: Prepare titanium source solution: select deionized water as solvent and chemically pure ammonium fluorotitanate as solute, prepare at room temperature, and the ratio is: solvent weight: solute weight = 1: 0.01483; Step 2: Prepare suspension: The liquid part of the suspension is titanium source solution, and the solid powder part is A2B7 rare earth hydrogen storage alloy powder. Prepare at room temperature, and the ratio is: titanium source solvent weight: solid powder weight = 1: x, and control the motor propeller stirrer stirring time to t1; Step 3: Coating reaction: The accelerator of the coating reaction is selected as chemically pure boric acid solid powder, the reaction stock solution is selected as the suspension containing A2B7 type rare earth hydrogen storage alloy powder in the second step, the reaction temperature is room temperature, the ratio of the accelerator to the solvent in the suspension is: the feeding weight of the solvent in the suspension: the feeding weight of the accelerator = 1: y, the stirring time of the motor propeller stirrer is controlled to be t2, the stirring is completed, and the static state is started, and the time interval from the start of the static state timing to the precipitation of all the precipitates in the coating reaction system to the bottom of the reactor is t3; Step 4: Cleaning of the coating: The three consecutive steps of the cleaning process are: Ⅰ. Centrifuge and remove the liquid from the precipitate. Use a centrifuge to dry the precipitate from the third step of the coating reaction; Ⅱ. Wash the precipitate. Rinse the precipitate dried by the centrifuge with deionized water three times; III. Vacuum drying: put the precipitate washed with deionized water into a vacuum drying oven, start the mechanical pump to evacuate and set the drying temperature to T1 and the drying time to t4; after the oven is cooled to room temperature, fill it with argon gas, open the oven door and take out the dried product to obtain the target product, titanium dioxide coated A2B7 type rare earth hydrogen storage alloy powder for nickel-metal hydride battery negative electrode; The weight of the titanium source solvent in the second step: the weight of the solid powder = 1: x, x range: x = 0.0167 ± 0.0033; the stirring time of the motor propeller stirrer is controlled to be t1, t1 range: t1 = 5 minutes ± 2 minutes; the solid powder part selects the A2B7 type rare earth hydrogen storage alloy powder, and the chemical formula of the A2B7 type rare earth hydrogen storage alloy powder is Ln 0.8 Mg 0.2 Ni 3.5 Al 0.3 Zr 0.05 ; The Taylor standard sieve sieving system for powder particle size is 200 mesh ± 50 mesh or 300 mesh ± 50 mesh; In the third step, the weight of the solvent in the suspension: the weight of the accelerator = 1: y, y range: y = 0.0123 ± 0.0003; the stirring time of the motor propeller stirrer is controlled to be t2, t2 range: t2 = 9 hours ± 3 hours; the standing time is t3, t3 range: t3 = 6 hours ± 2 hours; In the fourth step, the drying temperature is set to T1, and the range of T1 is: T1 = 50°C ± 10°C; Set the drying time to t4, t4 range: t4 = 12 hours ± 4 hours.
Citation Information
Patent Citations
Conductive tio2 / pa composite material and preparation method thereof
CN103849137B
High-power wide-temperature-zone power nickel-hydrogen battery
CN104600375A
Method for preparing conductive titanium dioxide whiskers
CN104630898A
A method for preparing conductive titanium dioxide powder
CN105271389B
Preparation method of inorganic light-colored conductive titanium dioxide powder
CN107903664A